THEORETICAL AND PRACTICAL IMPLICATIONS OF COMMUNICATION COMPETENCE IN A FOREIGN LANGUAGE - Lilia PETRICIUC (National Centre for Policy and Evaluation in Education, 2017)
The concept of communicative competence has been the essence of numerous studies for over 50 years. Despite this, it still represents an attractive topic of research for many professionals both due to its importance and because of multiple confusions created by various interpretations of its meanings. The aim of this article is to throw light on some theoretical aspects that apply to the communicative competence, its components as approached in several models as well as teachers' role and responsibility in its holistic development through selecting adapting and offering relevant educational materials.